Screening of Biosurfactant-Producing Bacteria as a Potential Biological Control Agent for Fungal Orchid Pathogens in Thailand - Chanika Saenge Chooklin,; Rattanapan, Natthaporn; Saimmai, Atipan; Riansa-ngawong, Wiboon; Maneerat, Suppasil (Science & Technology Asia, 2023)
In southern Thailand, biosurfactant-producing bacteria were isolated from palm oil mill facility soil using serial dilution. Palm oil mill effluent (POME) was utilized as the sole carbon source. A total of 231 oil-degrading bacterial isolates were discovered from 40 samples. Based on the examination of surface tension reduction and emulsification activities, 30 isolates showed promising biosurfactant activities; however, only 85 of the isolates tested positive for the formation of biosurfactants based on the oil displacement test. The biosurfactants from 30 bacterial isolates were tested for their antifungal efficacy against Phytophthora palmivora Al2 using an agar well diffusion assay. The strongest antifungal activity was seen in the biosurfactants produced from strain CT03. Analysis of the bacteria's 16S rRNA gene revealed the strain to be Acinetobacter calcoaceticus. It was discovered that MSM containing (NH4)2SO4 and glucose acting as carbon and nitrogen sources, respectively, provided the best conditions for A. calcoaceticus CT 03 to produce biosurfactants. A combination of chloroform: methanol (2:1, vol/vol) was used to extract 1.75 g/L of biosurfactant. The structures of the resulting biosurfactant compounds was determined using three distinct methods of spectroscopy: Fourier transform infrared (FT-IR), nuclear magnetic resonance (NMR), and mass spectroscopy. Additionally, the biosurfactants created by A.calcoaceticus CT 03 contained molecules of a lipopeptide that resembled surfactin. This study indicates the ability of this biosurfactant mixture to prevent pathogenic fungal growth in orchids.